Analisa Pengaruh Variasi Diameter Pipa Tekan PVC Pada Pompa Rotari Untuk Kecepatan Gaya Dorong Air - Rega Yuan Pradhana; Edi Widodo (Universitas Muhammadiyah Sidoarjo, 2017)
This research is aimed to analyze the effects of the PVC rotary pipe’s diameter to the velocity of the viscous forces. The diameter of the PVC rotary pipe used in this research are (1 ½”, 1”, ¾”, ½” inch). The procedure of this reasearch is begin with designing the pipe’s installation, then continued with the pipe installation, then continued with data recording. After the data is collected from the experiment, analyzing the data is needed. Also, calculate if there’s any effects of the velocity of the viscous forces due to the changing of the dependent variables (which is the diameter of the PVC rotary pipe). In the process of the fluid conduction inside the pipe, head losses are usually happened. The manual calculation needed to complete the research are, surface area calculation, fluid velocity calculation, reynold number calculation and coeff. Losses calculation. After all of the calculation are collected, the result of the research will be obtained. After that, discussion and conclusion can be produced.